(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Synthetic osteotropic substances are increasingly being utilized to address bone deficiencies within dental practices. These materials are engineered to encourage bone formation and integration, providing essential support for dental implants and other restorative procedures. Their biocompatibility and ability to mimic the natural properties of bone make them valuable in overcoming challenges presented by defects or loss of bone tissue.